Design, analysis and fabrication of manual food slicer machine / Muhammad Fareed Johari and Raja Muhammad Aslam Raja Arif - Johari, Muhammad Fareed; Raja Arif, Raja Muhammad Aslam (School of Mechanical Engineering, 2022)
Food preparation is vital in the food industry and in domestic use. Common problem faced by people in preparing food using a normal knife is usually regarding the safety issue and time consuming. Therefore, the objective of this project is to design, analyse, and fabricate the manual food slicer machine that intends to solve the problem. Using the imported food processor is not viable to many people due to the expensive cost. Hence, in this project, the manual food slicer machine is designed and fabricated to aid food preparation especially for vegetables and fruits. The development of this machine began by identifying problems that occur to many people in terms of food preparation. Then, market research is conducted to study the existing product. After that, the machine is designed based on the concept adapted from the problems faced. The material is picked carefully to ensure the hygienic and safety concern to the user. The fabrication processes include drilling, cutting, and fitting took place for almost 8 weeks. The result from the demonstration showed that the product assists the user significantly in terms of safety and quantity while performing the food preparation.